2016
DOI: 10.2147/ott.s115438
|View full text |Cite
|
Sign up to set email alerts
|

Cancer: fundamentals behind pH targeting and the double-edged approach

Abstract: The highly regulated pH of cells and the less-regulated pH of the surrounding extracellular matrix (ECM) is the result of a delicate balance between metabolic processes and proton production, proton transportation, chemical buffering, and vascular removal of waste products. Malignant cells show a pronounced increase in metabolic processes where the 10- to 15-fold rise in glucose consumption is only the tip of the iceberg. Aerobic glycolysis (Warburg effect) is one of the hallmarks of cancer metabolism that imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 153 publications
0
67
0
1
Order By: Relevance
“…As an adjuvant alternative, thermotherapy has been traditionally used to kill tumor cells in two different ways: on the one hand by hyperthermia, in which the temperature of a local region or the whole body is increased up to 41–45 °C by ultrasounds, microwaves, or radiofrequency radiation; on the other hand, by thermal ablation, in which a temperature above 45 °C is applied to the diseased area of interest that destroys the tissue . Both methods are based on the more thermosensitive character of the cancer cells compared to the healthy ones, due to its high glycolytic activity and consequent lower pH . However, these conventional technologies resulted to be very aggressive and suffer from low penetration depths and limited targeting.…”
Section: Representative Biomedical Applicationsmentioning
confidence: 99%
“…As an adjuvant alternative, thermotherapy has been traditionally used to kill tumor cells in two different ways: on the one hand by hyperthermia, in which the temperature of a local region or the whole body is increased up to 41–45 °C by ultrasounds, microwaves, or radiofrequency radiation; on the other hand, by thermal ablation, in which a temperature above 45 °C is applied to the diseased area of interest that destroys the tissue . Both methods are based on the more thermosensitive character of the cancer cells compared to the healthy ones, due to its high glycolytic activity and consequent lower pH . However, these conventional technologies resulted to be very aggressive and suffer from low penetration depths and limited targeting.…”
Section: Representative Biomedical Applicationsmentioning
confidence: 99%
“…While a single genetic mutation, amplification or deletion is insufficient to cause metastasis, the accumulation of ROS through Fenton reactions can stimulate widespread modifications to DNA, proteins and lipids which promotes a more aggressive tumor phenotype. ROS induce metabolic rewiring in cancer cells toward glycolysis, a feature described as the "Warburg effect, " however, the byproducts of this process increase intracellular acidity and in response, protons are exported into the extracellular space creating an acidic microenvironment (4). The acidic environment breaks down the extracellular matrix (ECM), promotes neo-vascularization, suppresses T cell activity and induces migration and invasion (4).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several studies have shown antitumor effects of V-ATPase inhibitors in preclinical tests. (15)(16)(17)(18) However, their clinical use as anticancer drugs has not been realized, possibly owing to the high toxicity of these inhibitors in humans, as discussed by Koltai et al (19) Therefore, in cancers that are highly susceptible to V-ATPase inhibition, this may be a useful new cancer therapeutic option. We considered that V-ATPase inhibitors may be beneficial in certain patients, and the identification of markers for patient selection may increase the probability of clinical success.…”
mentioning
confidence: 99%